Deciphering the source contribution of organic matter accumulation in an urban wetland ecosystem. (11th July 2022) - Dar, Shahid Ahmad; Bhat, Sami Ullah; Rashid, Irfan; Kumar, Pankaj; Sharma, Rajveer; Aneaus, Sheikh
Abstract: A better understanding of the organic matter (OM) dynamics is a key to successful wetland management. We established the radiocarbon chronology ( 14 C) and vertical distribution of nitrogen (N), phosphorus (P), OM, and carbon to nitrogen ratio (C/N) in the sediment core retrieved from the Anchar Wetland, Kashmir Himalaya. The accelerator mass spectrometer (AMS) assisted 14 C dating of the sediment core showed 14 C age reversals related to occasional disturbances. The vertical distribution of various fractions revealed increased concentrations of organic carbon (OC), OM, and nutrients (N and P) in the upper part of the sediment core, largely related to increased anthropogenic inputs from the catchment areas during recent decades. Further, the low to high C/N ratio (1.3–36.4) suggests a combination of both the autochthonous and allochthonous inputs as the major contributors of OM to the wetland ecosystem. The linear regression model showed significant ( p < 0.05) positive and negative relationships among various analyzed parameters. Principal component analysis (PCA) resulted in three principal components (PCs) accounting for a cumulative variance of 83.6%. The PCA suggests that the primary production, human activities such as extraction of Lotus stems ( Nadru ) and fishing, and terrestrial inputs (sewage disposal and fertilizer runoff) are the major factors controlling the distribution of organic fractions and nutrients. This study provides important insights into the sources and distribution of sedimentary OM and nutrients crucial for assessing the risks of pollution and for adopting the socially, politically, and scientifically robust strategies for the management of wetlands.